PRESUPPOSITION TRIGGERS IN THE WASHINGTON POST AND LOST ANGELES TIMES ONLINE NEWS - Khairani Ade Guswita; Pratomo Widodo (Center of Language and Cultural Studies, 2019)
The aim of this study is to analyze the use of presupposition triggers in the Washington Post and Los Angeles Times online news. This study was conducted using a qualitative approach. The sources of this study are the Washington Post and Lost Angeles Times news on the internet. The data were analyzed based on the theory about presupposition triggers from Levinson (1983) and Yule (1996). The data collection method in this study is Metode Simak and Metode Catat which are proposed by Sudaryanto (2018). The result of this study is the most dominant types of triggers presuppositions which found in the Washington Post online news is a definite description with 29 occurrences (26%) and 37 occurrences (24%)in Lost Angeles online news. Both the Washington Post and Los Angeles Times online news use the clef-construction as part of the lexical and non-restrictive clause as part of structural which more dominant than others. Otherwise, the distinction on two online is conventional times which only appeared in the Los Angeles Times.